2017
DOI: 10.1177/0022022117696802
|View full text |Cite
|
Sign up to set email alerts
|

Imagining Her Future: Diversity in Mothers’ Socialization Goals for Their Adolescent Daughters

Abstract: According to developmental niche theory, members of different cultural and ethnic groups often have distinct ideas about what children need to become well-adapted adults. These beliefs are reflected in parents’ long-term socialization goals for their children. In this study, we test whether specific themes that have been deemed important in literature on diverse families in the United States (e.g., Strong Black Woman [SBW], marianismo, familismo) are evident in mothers’ long-term socialization goals. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Black women may consider “strength” to be an integral part of womanhood21 and may believe that they must cope independently, eschewing help, when they face challenges such as physical disabilities 42. Oshin and Milan43 and Ramirez et al44 suggested that the SBW construct seems to provide Black mothers a parenting “curriculum,” dictating skills and traits to instill in their adolescent daughters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Black women may consider “strength” to be an integral part of womanhood21 and may believe that they must cope independently, eschewing help, when they face challenges such as physical disabilities 42. Oshin and Milan43 and Ramirez et al44 suggested that the SBW construct seems to provide Black mothers a parenting “curriculum,” dictating skills and traits to instill in their adolescent daughters.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen articles (40%) [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] were survey studies. Four studies (9%) 3,[42][43][44] used a mixed-methods design, and 4 (9%) [45][46][47][48] were studies to develop an instrument to measure SBW belief. Most studies (n = 32, 62%) included an age range of 20 years and more (often young adult to elderly), while 9 studies (19%) 2,16,23,25,26,[32][33][34]38 focused on adolescents (aged 12-18 years), young women (aged 17-30 years or mean age of 19-22 years), or women in their childbearing years (aged 18-40 years), depending on the phenomenon studied.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…However, less research is available on parents' beliefs about youth. The few available studies are often based on North American parental reports, for example, concerning youth socialization goals (Ramirez et al, 2017;Richman & Mandara, 2013) or youth well-being (Alberts et al, 2006;King et al, 2005). The little existing qualitative studies on what youth well-being means to North American mothers and fathers, depict cognitive, physical and socio-emotional strengths of youth and their engagements with activities and people in their contexts, although with variations in what is emphasized.…”
Section: Parent's Beliefs About Youth Well-being: Ethnotheories Consideredmentioning
confidence: 99%
“…For example, Ramirez et al. (2017) conducted interviews with Black mothers and daughters in the U.S. to examine how the expectation of the SBW is transferred through generations. Results showed that mothers emphasized the importance of their daughters showing strength and self‐reliance.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of family socialization indicate that Black mothers express aspirations that their daughters develop strength, independence, and a willingness to help others(Shambley-Ebron et al, 2016). For example,Ramirez et al (2017) conducted interviews with Black mothers and daughters in the U.S. to examine how the expectation of the SBW is transferred through generations. Resultsshowed that mothers emphasized the importance of their daughters showing strength and self-reliance.…”
mentioning
confidence: 99%